Controlled gelation kinetics of cucurbit[7]uril-adamantane cross-linked supramolecular hydrogels with competing guest molecules - Chen, Hao (Sci Rep, 2016)
Gelation kinetics of hydrogels is closely linked to many applications such as the development of injectable and printable hydrogels. However, the control of gelation kinetics without compromising the structure and other properties of the hydrogels, remains a challenge. Here, we demonstrate a method to control the gelation kinetics of cucurbit[7]uril-adamantane (CB[7]-AD) cross-linked supramolecular hydrogels by using competing guest molecules. The association between CB[7] and AD moieties on the polymer backbone was impeded by pre-occupying the CB[7] cavity with competing guest molecules. By using various guest molecules and concentrations, the gelation of the hydrogels could be varied from seconds to hours. The strong interaction of CB[7]-AD pair endue the hydrogels good mechanical properties and stability. Moreover, the binding of functionalized guest molecules of CB[7] moieties offers a facile approach for tailoring of the hydrogels’ scaffold. Combined with hydrogel injection and printing technology, this method offers an approach for the development of hydrogels with advanced temporal and spatial complexity.